AN ERROR ANALYSIS IN GENERATING COMPOUND COMPLEX SENTENCE ON STUDENTS’ WRITING - Euis Kurniasih (FKIP, Universitas Banten Jaya, 2022)
Since compound-complex sentences combine two distinct sentences, many students face difficulties to generate the type of sentence. This research aims to analyze the students’ errors in writing compound-complex sentences. The research applied the descriptive qualitative research design. The participants of the research are English education department students taking basic writing course. The data was taken from student’s writing task and analyzed classifying them into different types of sentence errors based on Hacker and Sommers (2011). The result shows that the error made by students are fused sentence 35.6 %, missing verb 28%, missing subject 20%, comma splices 13,3% and missing subject and verb 2,2%. It is advised that the lecturers in writing classes provide more tasks in addition to demonstrating more frequent errors and examples of compound-compound complex phrases taken from real-world texts.